Virna Glaucoma Implant (VGI) as the Management of Secondary Glaucoma following TASS : A Case Report: Poster Presentation - Case Report - General practitioner - Presialia, Athira; Witjaksono, Anissa Nindhyatriayu; Anissa, Gisela Haza; Widyawati, Syska (Majalah Oftalmologi Indonesia, 2023)
Introduction : Secondary glaucoma may occur in severe TASS. The inflammatory cell and debris can clog trabecular meshwork causing IOP to rise. In this case, we describe the successful management of secondary glaucoma due to TASS using Virna Glaucoma Implant (VGI). Case Illustration : A 66-year-old woman presented with decreased vision in the left eye one week after anterior vitrectomy and anterior segment lavage due to TASS. She had a history of phacoemulsification and intraocular lens placement with complication of PCR. On ocular examination, the visual acuity was 1/60 in the left eye with intraocular pressure (IOP) 55 mmHg. After maximum glaucoma medication using timolol, latanoprost, brinzolamide eye-drops and oral acetazolamide IOP was 22mmHg. Glaucoma Drainage Device (GDD) surgery using VGI was performed. After 2.5 weeks, IOP in the left eye was reduced to 19 mmHg without anti-glaucoma medication and visual acuity has improved to 6/60, showing a favourable outcome. Discussion : TASS may cause significant damage to the trabecular meshwork, which leads to secondary glaucoma. Although medical therapy is often used to control elevated IOP, surgical therapy may be required to treat refractor IOP elevation. GDD surgery has been reported to have effective outcomein secondary glaucoma and pseudophakic eyes. Conclusion : Secondary glaucoma is considered as one of the characteristics in the late stages of TASS, and required prompt treatment. VGI implantation is a promising choice of treatment in managing secondary glaucoma following TASS when medication is not effective.